Information security as exemplified by the crime of espionage in the Polish and Swedish criminal law - Rosicki, Remigiusz (Instytut Nauk Politycznych Uniwersytetu Warszawskiego, 2018)
The objective scope of the analysis contained in the text concerns legal solutions to penalisation of the crime of espionage with regard to information security. As the main goal, the text performs an analysis of the crime of espionage in the Polish substantive penal regulations, including a comparative analysis of corresponding Swedish substantive penal regulations. In order to elaborate the research problem, the text addresses the following research questions: (1) To what degree do the legal solutions concerned with the penalisation of the crime of espionage provide effective prosecution and combating of this type of crime? (2) What changes in the scope of legal solutions penalising the acts of espionage can be proposed? While the analysis contained in the text is for the most part a dogmatic and doctrinal approach, a comparative interpretation (with regard to substantive penal regulations penalising the crime of espionage in Poland and Sweden), as well as teleological and functional interpretations (with a view to reinterpreting selected, established or debated doctrinal approaches) are also applied.
The objective scope of the analysis presented in the text concerns a selection of legal ,,regulations penalising the crime of espionage. The main objective of the text is to present selected substantive penal aspects of the crime of espionage in accordance with the legal regulations in Poland and Sweden. The comparative analysis places greater emphasis on the Polish legal solutions. The text poses the following research questions, which have been associated with specific conclusions: (1) To what degree do the legal solutions concerned with the penalisation of the crime of espionage provide effective prosecution and combating of this type of crime? It should be noted that the content of Art. 130, which penalises the crime of espionage in the Polish Criminal Code, raises doubts on account of interpretation and effective combating of espionage incidents directed against the Republic of Poland. The main interpretative problems include: (1) the Polish legislator’s use of the term “intelligence,” which narrows the acts of espionage down to activity for the benefit of a specified subject, (2) the Polish legislator’s use of the wording “against the Republic of Poland,” which makes it difficult to prosecute spying activity not displaying any action aimed directly against the Republic of Poland or third states, (3) the Polish legislator’s use of the wording qualifying information “the transfer of which may be detrimental to the Republic of Poland,” which gives rise to a high degree of subjectivity while assessing damage, (4) the adoption in the interpretative doctrine of the attribute of “declaring a readiness to work for the benefit of a foreign intelligence service” as specification of the attributes of criminal preparation – “establishing communication,” which results in the necessity to prove the response/acceptance of the proposal on the part of a foreign intelligence service. All these descriptive and evaluative attributes may hamper effective prosecution and combating of espionage. (2) What changes in the scope of legal solutions penalising the acts of espionage can be proposed? With regard to the performed analysis of the main attributes of the crime of espionage in its basic, autonomous and privileged forms in the Polish criminal regulations, and with regard to the comparative analysis of the Swedish criminal regulations, it should be concluded that: (1) the regulations penalising acts of espionage and acts directed against information protection (including acts termed “cyberterrorism”) need to be amended, (2) there is a need for systemic solutions as regards acts aimed against the state and information protection, (3) it is necessary to replace the attribute of “a foreign intelligence service” with the attribute of “a foreign state” or “a foreign authority,” i.e. it is necessary to introduce a solution that features in the Swedish, Serb and Croatian regulations, (4) it is necessary to change the privileged form as regards the extension of criminal liability to cover various forms of preparation for the crime of espionage, (5) it is necessary to change the privileged form of the crime of espionage as regards the attribute of “declaring a readiness to work for the benefit of a foreign intelligence service” so as to eliminate the doctrinal interpretation of the current legal solution, (6) it is necessary to introduce regulations penalising the very fact of declaring a readiness to act for the benefit of a foreign state against the Republic of Poland, (7) it is worth considering minimizing the significance of the term ‘damage’ in favour of case-law definition of a kind of information as the object of a crime, (8) following the solutions in the Swedish regulations, it is worth considering introducing specified forms of the crime of espionage in view of the violation of caution principles, although this might result in too high a degree of legislative restrictiveness, (9) following the solutions included in the Swedish regulations, it is worth considering introducing penalisation of various forms of intelligence activity as opposed to the crime of capital espionage, (10) following the solutions included in the Swedish regulations, it is worth introducing penalisation of various forms of foreign support, whereby acts which might be termed illegal financial assistance, illegal support for agents of influence, or illegal activities concerned with exerting influence on public opinion as regards matters of major relevance for the state.
Keywords: Bezpieczeństwo państwa; State security; Bezpieczeństwo informacji; Information security; Szpiegostwo; Espionage; Przestępstwo szpiegostwa; Crime of espionage; Działalność szpiegowska; Spying activity; Działalność wywiadowcza; intelligence activities